Gentil filha do mar: a experiência do espaço marítimo na poesia de Maria Firmina dos Reis - Patricia Fernanda Massetti de LIMA (2023)
The poetry of Maria Firmina, an outstanding writer of the 19th century, reveals a deep connection with important themes, such as the relationship with nature and a latent concern with the social and cultural issues of her time. In this work, we propose an analysis of Firmina's poems under complementary perspectives: the poetics of landscape by Michel Collot (2013), the perspective of construction by Gaston Bachelard (1999, 2005, 2008) with a phenomenological approach and the symbolic approach by Alain Gheerbrant and Jean Chevalier (2009). By exploring the author's relationship with nature and the symbols that permeate her work, we seek to shed light on the complexity and richness of these texts, revealing their multiple layers of meaning. Nature, for Firmina, is a space where symbols emerge and come to life, revealing the nuances of human emotions and social realities. The union of these perspectives enriches the understanding of the author's intentions, offering a deeper and more holistic view of her poetry. In addition to the aforementioned authors, we base ourselves on the work of Eric Dardel (2011), an important geographer for organizing and substantiating the ideas proposed by phenomenological Geography, Yi-Fu Tuan (2013), an experienced writer who revealed through his productions that the experience is a guiding element for apprehending the concepts of place and space, as well as the feeling of belonging. These authors were used for the theoretical understanding of the theme, as well as its application in the analyses, however, we cannot fail to mention relevant authors to understand the author's biographical aspects, as well as her insertion in the literary universe, in this way, we quote José Nascimento de Morais Filho (1975), Dilercy Adler (2015) and Agenor Gomes (2021). In the end, the proposed analysis not only highlights the relevance of Maria Firmina's poetry, but also invites us to explore the layers of meaning that permeate her verses. His ability to merge his subjectivity with nature with a bias towards symbolic construction reflects not only his skill as a poet, but also his commitment to addressing issues that are part of human construction.